Evaluating postoperative complications in radical cystectomy and ileal conduit for bladder cancer using the clavien-dindo grading system - Ullah, Shuah; Gul, Laraib; Yousuf, Shariq Bin; Hassan, Bazgha; Tanzeel-Ur-Rahman Gazder; Hassan, Asad Shahzad (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of postoperative complications after radical cystectomy with ileal conduit surgery in patients diagnosed with urinary bladder cancer. Method: This prospective observational study was conducted at the Department of Urology, Sindh Institute of Urology and Transplantation (SIUT), Karachi, from 30TH December 2019 to 30TH June 2020, following approval from the SIUT Ethical Review Board. The study comprised patients aged 25-70 years diagnosed with urinary bladder cancer who underwent elective radical cystectomy with ileal conduit. Complications were compared with respect to preoperative characteristics, such as disease stage, chemotherapy, radiotherapy, and intraoperative variables, like operation time, predicted blood loss, and the requirement for blood transfusion, as well as postoperative therapies. All postoperative complications occurring within a 60-day period were classified using the Clavien-Dindo grading system. Data was analysed using SPSS 22. Results: Of the 34 patients, 22(64.7%) were males and 12(35.3%) were females. The overall mean age was 51.00±12.84 years. Grade 0 complications were observed in 14(41.18%) patients, grade 1 13(28.24%), grade 2 3(8.82%), grade 3a 2(5.88%), and grade 4a 2(5.88%). The severity was significantly associated with female gender, preoperative irradiation, larger volume of blood loss, and the required of numerous transfusions (p<0.05). Conclusion: The early complications of radical cystectomy and urinary diversion had a substantial impact on the overall success of the procedure. Key Words: Radical cystectomy, Ileal conduit, Clavien-Dindo classification.